Diagnosis, management, and outcomes of brain abscess due to gram-negative versus gram-positive bacteria. (February 2022) - Corsini Campioli, Cristina; Castillo Almeida, Natalia E.; O'Horo, John C.; Wilson, Walter R.; Cano, Edison; DeSimone, Daniel C.; Baddour, Larry M.; Sohail, M. Rizwan
Highlights: Despite our approach to brain abscess management, morbidity and mortality remain high. Brain abscess due to gram-negative bacteria is infrequent and these patients are more likely to have undergone a prior head and neck surgery [Au?1]. Patients with gram-negative bacteria had a higher therapeutic failure rate than those with gram-positive bacteria. Abstract: Objectives: Differences in management and outcomes of brain abscesses due to gram-positive (GPB) versus gram-negative bacteria (GNB) are not well defined. Methods: A retrospective review of adult patients with brain abscesses due to monomicrobial infection from 2009 through 2020 was performed. Results: A total 177 patients had a monomicrobial brain abscess; 143 (80.8%) caused by GPB and 34 (19.2%) by GNB. Patients with GNB had more history of head/neck surgery than those with GPB (58.8% vs 36.4%; P  = 0.02). Pathogens in the GNB group included Pseudomonas aeruginosa (29.4%), Klebsiella spp (20.6%), and Enterobacter spp (20.6%). Pathogens in the GPB group included Staphylococcus aureus (32.2%) and Streptococcus spp (31.5%). Most patients had combined medical/surgical management (64.7% GNB vs 63.6% GPB). The median duration of antibiotic therapy was 42 days, and there was no significant difference in infection relapse or 3-month survival rate. Patients with GNB were more likely to have therapeutic failure than those with GPB (44.1% vs 22.4%; P  = 0.01). Conclusions: Compared with brain abscesses caused by GPB, those due to GNB were more likely to occur in patients who had undergone prior head and neck surgery . No statistically significant difference in outcomes was observed between the groups; however, patients with GNB had a higher therapeutic failure rate than those with GPB.